Effectiveness of Russia's cyberaggression against Ukraine in 2022/2023 - Agnieszka Bógdał-Brzezińska (Przegląd Geopolityczny)
The purpose of this article is to examine the determinants and evaluate the effectiveness of the impact of cyber measures used during the Russian-Ukrainian war. The analysis is primarily concerned with the subject dimension, in order to show that the cyber dimension of this war involves not only the parties to the kinetic conflict, i.e. Russia and Ukraine. Therefore, both non-state actors and international institutions, as well as state actors supporting Ukraine, will be assessed. The conclusions indicate that as a conflict in cyberspace, this war is not a bilateral conflict, but a multilateral one with changing dynamics, in which the number and type of combatants also change.